Sistem Pengaman Peralatan Listrik PLN untuk Keselamatan Manusia Dalam Rumah Tinggal di Pedukuhan Suren Wetan - Suyanto, Muhammad; Syafriyudin (LPPM IST AKPRIND Yogyakarta, 2021)
Man was created by God with the power to conduct electricity. However the human body still has limitations. The effect of electric shock on the human body is not the same as the reaction, depending on the magnitude of the electric current that passes through the human body is less than 1 mA, the sensation of shock is only felt in the hand. Above 3 mA, it is in the form of a surprise that feels sick and results in an accident. 10 mA or more, the muscle becomes stiff until it can't remove the condenser. If more than 30 mA, paralysis occurs in the respiratory muscles (lungs). At 100 mA to 4 A, it must interfere with the rhythm of one of the heart chambers (ventricles). The potential danger of being electrocuted (Electric shock), being attacked by a spark (Arc Flash) and an explosion of sparks (Arc Blast), is a serious risk problem. The spark triggers an electric short circuit with an Arc Flash level above (10,000 F), hotter than the surface of the sun, which can cause burns to the human body. In order for the user to use the equipment, the equipment and the environment is quite safe, then the safety of humans for the use of electrical energy in the residence, gets a sense of security and from the dangers of danger due to electric accidents. To reduce and prevent unwanted things from happening, regulations, symbols / codes and other signs are made as guidance.